1, 25‐Dihydroxyvitamin D3 and its analogues increase catalase at the mRNA, protein and activity level in a canine transitional carcinoma cell line. (6th November 2013) - Middleton, R. P.; Nelson, R.; Li, Q.; Blanton, A.; Labuda, J. A.; Vitt, J.; Inpanbutr, N.
Abstract Antioxidant enzymes, such as catalase, superoxide dismutases (SOD), MnSOD and Cu/ZnSOD, protect cells by scavenging reactive oxygen species (ROS). Numerous studies have reported the anti‐cancer effects of 1, 25‐dihydroxyvitamin D3 (calcitriol) and its related analogues, seocalcitol and analogue V. In this study, canine bladder transitional cell carcinoma (cbTCC) cells were used to determine effects of calcitriol and its related analogues on antioxidant enzyme gene expression, protein expression and activity. Catalase mRNA was increased in response to calcitriol (10−7 M), and seocalcitol (10−7 and 10−9 M). MnSOD mRNA was decreased in response to calcitriol at 10−7 M. Catalase was significantly increased in response to calcitriol (10−7 and 10−9 M), and seocalcitol (10−9 M). Catalase enzymatic activity increased in response to calcitriol, seocalcitol and analogue V (10−9 M). In addition, global gene expression analysis identified the involvement of mitogen‐activated protein kinase (MAPK) signalling in cbTCC's response to calcitriol and seocalcitol treatment.